Ultrassonografia convencional e Doppler da glândula mamária de caprinos para diagnóstico de mastite - Santos, Victor José Correia [UNESP] (2014)
It’s suggested that both B-mode and Doppler ultrasonography could be used to obtain the diagnosis of mastitis in goats on a trustful and non-invasive way, therefore, this study aims to evaluate the sonographic characteristics of the udder and teats and to determine the Doppler indexes of mammary artery at its bifurcation in healthy animals, as well as in animals with both subclinical or clinical mastitis. Thirty animals among Saanen and Alpine Brown goats aged between 2 and 5 years were arranged in three groups, healthy animals (GS), animals with subclinical mastitis (GMSC) and animals with clinical mastitis (GMC). The animals underwent clinical examinations to verify the occurrence of mastitis. The milk was evaluated using the strip cup test and California Mastitis Test (CMT). Using the B-mode, the sonographic characteristics (echotexture and echogenicity) and biometry (diameter and area of the udder cistern, diameter and area of the teat cistern and thickness of the teat wall) were evaluated. Using Doppler ultrasonography, the vascular indexes of the mammary artery were obtained. It was observed hiperecogenicity with solid component in the gland cistern when comparing animals with clinical mastitis and healthy mammary tissue. Regarding the echotexture of the breast tissue, there was heterogeneity in the mammary parenchyma on the three groups, for the milk, it was observed homogeneity for animals on GS and GMSC and heterogeneity for animals on GMC. Grey-scale quantitative assessment revealed increase in echogenicity (mean value) for all the structures when comparing the three groups. Biometry didn’t reveal statistical difference between groups, for none of the evaluated structures. Doppler examination of the mammary artery showed the decrease of final diastolic velocity (VDF) and raise of pulsatility index (IP) between groups. The association of B-mode and Doppler ultrasonography is useful for the evaluation of the udder of ...